EDITORIAL: Killing the messenger - David Robie (Asia Pacific Network, 2018)
The statistics globally are chilling. And the Asia-Pacific region bears the brunt of the killing of journalists with impunity disproportionately. Revelations in research published in this edition of Pacific Journalism Review on the trauma experienced by television journalists in the Philippines covering President Rodrigo Duterte’s so-called ‘war on drugs’, or as many describe it, a ‘war on poverty’, with more that 12,000 dead is deeply disturbing (Amnesty International, 2017). While these deaths, allegedly mostly extrajudicial killings, do not relate directly to the murders of journalists, the highest death toll ever of journalists in a mass execution took place in the southern Philippines almost nine years ago.